Ditadura, arquivo e memória: notas para um estudo sobre o caso Organização Política Operária (Polop) - Torres, Aline Camargo (2013)
This dissertation presents the debate on the archives’ process of social construction and its connection with the production and dissemination of memorial narratives, based on the study case of Política Operária (Polop) and the organization of its historic al archives by its former members. The aim is to shed light on how this group of people brings forth their archive, concerning both its materiality and the speech that involves its production. The analysis also includes the guarding institutions, the profe ssional workforce and the specific public policies, which influence the final aspects of these historical sources. Seen here mainly as the subject for investigation, instead of source, the archive is understood as part of a scenario in which the processes of reviewing the memory and the history produced during the military dictatorship (1964 - 1985) takes place. By concentrating efforts on understanding the role played by the archives as raw material for new historical narratives, the present research aims at questioning how these sources are produced and understanding how they achieve legitimacy as keys to comprehend the past.